2019
DOI: 10.15666/aeer/1703_64156427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Metal Pb and Cd Stress on Physiological Characteristics of Japanese Honeysuckle

Abstract: To evaluate physiological changes of Japanese honeysuckle under lead and cadmium stress, pot-plant experiment was adopted to discover heavy metal Pb or Cd single stress and Pb+Cd combined stress on part of physiological parameters of. Japanese honeysuckle. The results showed that under the same treatment, as time prolonged, the content of soluble sugar and soluble protein was decreased, the activity of SOD declined, the amount of free proline and MDA increased and the activity of CAT elevated. Under Pb stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The protein content of A bisporus in the closed cup stage was higher than that in the flat stage, while the soluble sugar content had the opposite change. The reason might be that under heavy metal stress, the absorption of some essential ions is weakened, resulting in the accelerated decomposition of substances such as starch, protein, and nucleic acids 39 . The decomposition of starch results in an increase in soluble sugar content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein content of A bisporus in the closed cup stage was higher than that in the flat stage, while the soluble sugar content had the opposite change. The reason might be that under heavy metal stress, the absorption of some essential ions is weakened, resulting in the accelerated decomposition of substances such as starch, protein, and nucleic acids 39 . The decomposition of starch results in an increase in soluble sugar content.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found in rice under Zn or Cr stress 35 . Soluble sugar, as the main osmotic agent, has a stabilizing effect on the cell membrane and protoplasmic colloid under heavy metals stress 39 . Most of the previous reports have found the content of soluble sugar in the body increased under heavy metals stress 35,40 .…”
Section: Effect Of CD Stress On the Cd Bioaccumulation Bcf And Tf In ...mentioning
confidence: 99%
“…4). Although many experiments showed that the activity of SOD increased with the concentration of Cd and PB under single and combined stress, some previous studies also showed that Pb or Cd inhibited the SOD activity, who concluded that it may be the dynamic balance of ROS is broken by the excessive accumulation of ROS under elevated concentrations of heavy metal stress in plants [48,49]. Heavy metals could produce severe toxicity symptoms which destroyed the antioxidant enzyme system in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic excitation effect is a plant phenomenon that can be characterized by an inverse U-shaped curve in which modest concentrations of hazardous chemicals have a stimulatory impact [40]. Hon-eysuckle has been shown to alleviate the effects of heavy metal stress on plant metabolic disorders by boosting leaf osmoregulatory chemicals and triggering the reactive oxygen species scavenging mechanism under a specified range of heavy metal stresses [41]. Ginkgo biloba L. activated this mechanism to cause harmful excitatory effects in response to low concentrations of Pb and Cd stress in this investigation.…”
Section: Changes In Net Photosynthetic Ratementioning
confidence: 99%